Super-Eddington accretion of the first Galactic ultra-luminous X-ray pulsar Swift J0243.6+6124. Issue 4 (26th April 2022) - Liu, Jiren; Jenke, Peter A; Ji, Long; Zhang, Shuang-Nan; Zhang, Shu; Ge, Mingyu; Liao, Jinyuan; Li, Xiaobo; Song, Liming
ABSTRACT: We present a detailed timing study of the pulse profile of Swift J0243.6+6124 with Hard X-ray Modulation Telescope (HXMT) and Fermi /GBM (Gamma-ray Burst Monitor) data during its 2017 giant outburst. The double-peak profile at luminosity above 5 × 10 38 erg s −1 is found to be 0.25 phase offset from that below 1.5 × 10 38 erg s −1, which strongly supports for a transition from a pencil beam to a fan beam, and thus for the formation of shock dominated accretion column. During the rising stage of the high double-peak regime, the faint peak got saturated in 10–100 keV band above a luminosity of L t ∼ 1.3 × 10 39 erg s −1, which is coincident with sudden spectral changes of both the main and faint peaks. They imply a sudden change of emission pattern around L t . The spin-up rate ($\dot{ν }$ ) is linearly correlated with luminosity ( L ) below L t, consistent with the prediction of a radiation pressure dominated disc. The $\dot{ν }-L$ relation flattens above L t, indicating a less efficient transfer of angular momentum and a change of accretion disc geometry above L t . It is likely due to irradiation of the disc by the central accretion column and indicates significant radiation feedback well before the inner disc radius reaching the spherization radius.